1978
DOI: 10.1002/cite.330500404
|View full text |Cite
|
Sign up to set email alerts
|

Ionengleichgewichte in nichtwäßrigen Elektrolytlösungen

Abstract: Im Ansatz fur die Wechselwirkungsenergie vj ( r ) zwischen den Ionen eines Ionenpaares [Kz+ A'-]' ( z , = Iz-1 = z ) in Losung wird durch den Term U* den Nahwirkungskraften i m Ionenpaar Rechnung getragen. Aus der Temperaturabhangigkeit der Gleichgewichtskonstante K , der Ionenassoziation KZ+ + Az-s[KZ+AZ-]O wird die Moglichkeit gewonnen, zwischm Typen von Nahwirkungskraften zu unterscheiden. 1 Verteilungsfunktionen Die statistisch-mechanische Theorie betrachtet eine Elektrolytlosung zunachst als mechanisches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The critical distance range can be obtained by the Bjerrum theory, which usually is a criterion to evaluate whether the ion pair is formed or not where z i and z j are the number of cation and anion charges, k B is the Boltzmann constant, ε 0 is a dielectric constant of the vacuum, and ε is the dielectric constant of the solvent. In this work, the dielectric constant of solutions is computed using the Pottel model as follows in which ε is the dielectric constant of the solvent in the presence of electrolytes, ε s is the pure solvent dielectric constant, and ξ 3 ″ is a variable defined as in which N a is the Avogadro number, n i is the number of moles of ion i , σ is the diameter of ion i , and V is the solution volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical distance range can be obtained by the Bjerrum theory, which usually is a criterion to evaluate whether the ion pair is formed or not where z i and z j are the number of cation and anion charges, k B is the Boltzmann constant, ε 0 is a dielectric constant of the vacuum, and ε is the dielectric constant of the solvent. In this work, the dielectric constant of solutions is computed using the Pottel model as follows in which ε is the dielectric constant of the solvent in the presence of electrolytes, ε s is the pure solvent dielectric constant, and ξ 3 ″ is a variable defined as in which N a is the Avogadro number, n i is the number of moles of ion i , σ is the diameter of ion i , and V is the solution volume.…”
Section: Resultsmentioning
confidence: 99%
“…The critical distance range can be obtained by the Bjerrum theory, which usually is a criterion to evaluate whether the ion pair is formed or not 31…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Fuoss has shown that the simple model of charged spheres in a continuum fails completely when the ions are small compared to solvent molecules (90). In another study, models incorporating a term for short-range forces in calculating the energy of interaction between ions are discussed (25). The temperature dependence of the equilibrium constant for ion association permits distinction between different types of short-r¿mge forces.…”
mentioning
confidence: 99%